Functional Recovery in Balance and Mobility After Vestibular Rehabilitation in a Patient with Posterior Canal BPPV: An Case Report - Laksmita Dewi Adzillina; Alifa Dinda Nurrina; Ragil Aidil Fitriasari; Mianti Nurrizky; Aditya Hans Suwignjo (Lembaga Pengembangan Kinerja Dosen, 2025)
Benign paroxysmal positional vertigo (BPPV) is a common cause of peripheral vestibular dysfunction, often resolving with canalith repositioning maneuvers (CRM). However, residual dizziness and imbalance may persist, impairing functional mobility. This case report describes a 55 year old female diagnosed with right posterior canal BPPV through a positive Dix Hallpike test. Following successful CRM, she reported residual postural instability and difficulty walking. A structured four week vestibular rehabilitation therapy (VRT) program was implemented, consisting of habituation (Brandt Daroff), adaptation (gaze stability, VOR x1, VOR x2), sensory substitution, and progressive balance training, delivered three times weekly for 45 minutes per session. Balance and mobility were assessed using the Berg Balance Scale (BBS) and Timed Up and Go (TUG) test at baseline and after the intervention. Results showed improvement in BBS from 42/56 to 53/56 (+11 points) and a reduction in TUG from 14.8 to 9.6 seconds (−5.2 seconds), both exceeding minimal detectable change values for older adults. The patient reported complete resolution of dizziness, increased walking confidence, and return to independent daily activities without adverse effects. This case suggests VRT as a valuable adjunct to CRM in BPPV patients with residual functional deficits, warranting further research in larger controlled studies.